1999
DOI: 10.1046/j.1365-2672.1999.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ba813 chromosomal DNA sequence effectively traces the whole Bacillus anthracis community

Abstract: V . R AM I SS E, G . P AT R A, J. V AI SS A IR E A N D M . M O CK . 1999. Plasmid genes that are responsible for virulence of Bacillus anthracis are important targets for the DNA-based detection of anthrax. We evaluated the distribution of the Ba813 chromosomal DNA sequence (Ba813) within closely related Bacillus species. Ba813 was systematically identified from 47 strains or isolates of B. anthracis tested, thus indicating its reliability as a tracer for that species. From the 60 strains of closely related Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 23 publications
3
56
0
Order By: Relevance
“…These results showed that the primer set BA813-f/r was not specific for B. anthracis, which is consistent with previously published results where four out of 60 non-B. anthracis strains were amplified (Ramisse et al, 1999).…”
Section: Nucleotide Sequence Accession Numberssupporting
confidence: 82%
“…These results showed that the primer set BA813-f/r was not specific for B. anthracis, which is consistent with previously published results where four out of 60 non-B. anthracis strains were amplified (Ramisse et al, 1999).…”
Section: Nucleotide Sequence Accession Numberssupporting
confidence: 82%
“…30 These genetic markers provide limited specificity and require additional timeconsuming and labor-intensive post-PCR analysis steps. Other areas of the chromosome have also been investigated as potential DNA-targets for identification purposes, including the so-called BA813 [31][32][33][34][35][36][37][38] and BA5510 sequences, 19 genes bclB, 39 sap, 40,41 saspB, 5,42 and sspE, 22,43 the B-type small acid-soluble spore protein gene (SASP), 44 a glycosyltransferase group 1 family protein, 45 a protein showing similarities with an abhydrolase, 18 and several DNA loci located on prophage regions, 17 i.e., BA5345, 21 BA5357, 46 and PL3. 47 Although most of these regions have been claimed to be anthrax-specific, B. cereus strains sometimes yield false positive results.…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%
“…Assays mentioned by the World Health Organization (WHO) 31,40,44 were also included in the ring trial, as well as a hydrolysis probe assay 35 that targets the often used BA813 marker [31][32][33][34][35][36][37][38] (Table 3). The latter marker has shown in silico cross-reactions toward the near-neighbor strains in use in this trial and was included for this reason.…”
Section: Ring Trialmentioning
confidence: 99%
“…1A). A positive PCR result with the B. anthracis rpoB primers is not equivalent to B. anthracis identification (12,14,16). However, rpoB still retains value as a chromosomal marker since B. anthracis can lose both its virulence plasmids (1,11), although it is more likely to spontaneously lose pX02 (12).…”
mentioning
confidence: 99%